Differences in infant feeding practices between Indian-born mothers and Australian-born mothers living in Australia: a cross-sectional study - Chitra Tulpule; Miaobing Zheng; Karen J. Campbell; Kristy A. Bolton (BMC Public Health, 2022)
Abstract Background Immigrant children from low- and middle-income countries (e.g. India) have higher obesity rates than children from high-income countries (e.g. Australia). Infant feeding practices are a key modifiable risk factor to prevent childhood obesity. This study compared infant feeding practices such as breastfeeding, infant formula feeding, timing of introduction to other liquids and solids of Indian-born versus Australian-born mothers living in Australia. Methods Data of children aged between 0–24 months from the 2010–2011 Australian National Infant Feeding Survey were analysed. Infant feeding practices between Indian-born mothers (n = 501) and Australian-born mothers (n = 510) were compared. Multiple regression models with adjustments for covariates, such as maternal demographic factors, were conducted. Results Compared to infants of Australian-born mothers, infants of Indian-born mothers were breastfed for 2.1 months longer, introduced solids 0.6 months later and water 0.4 months later (p < 0.001). Moreover, infants of Indian-born mothers were 2.7 times more likely to be currently breastfeeding, 70% less likely to currently consume solids and 67% less likely to consume solids before six months (p < 0.001). In contrast, infants of Indian-born mothers were introduced to fruit juice 2.4 months earlier, water-based drinks 2.8 months earlier and cow’s milk 2.0 months earlier than infants of Australian-born mothers (p < 0.001). Additionally, infants of Indian-born mothers were 2.7 times more likely to consume fruit juice (p < 0.001) than the infants of Australian-born mothers. Conclusion Significant differences exist in infant feeding practices of Indian-born and Australian-born mothers (some health promoting and some potentially obesogenic). The evidence of early introduction of sweetened fluids in infants of Indian-born mothers provides an opportunity to support parents to delay introduction to promote optimal infant growth..